Ducting and piping designmodules for vocational college students - Razali, Nizamudin; Kusairi, Nur Ku Fatin Syahirah; Nur Yunus, Faizal Amin; Abdul Rahman, Khairul Anuar; Wan Muda, Wan Hanim Nadrah (Penerbit UTHM, 2021)
The use of Teaching Aids (ABBM) is a component that makes the Teaching and Learning process(PdP)successful. According to Brodin & Reinblad (2014), pedagogy developed should encourage the learning process and increase the student's desire to continue to learn. Additionally, effective and systematic teaching materials are capable of producing student-centered teaching (Morrison, Ross, Kalman & Kamp, 2010). Therefore, the researcher can identify that the use of appropriate and systematic ABBM can increase the students' desire in learning. Furthermore, the teaching materials used should be appropriate for the students to leave the best impact on learning and to motivate students to always engage in learning (Morrison, 2011).